Physiological Response and Haematological Profile of Reproductive Ewe Consuming Diet Supplemented with Black Tea Extract and Sunflower Seed Oil - Diapari, Didid; Hermana, Widya; Prameswari, Febrina; Jayanegara, Anuraga (ANIMAL PRODUCTION, 2017)
This study was aimed to examine the effect of black tea extract addition in diet containing 4% and 6% sunflower oil on ewe physiological responses and blood profiles from late pregnancy until early lactation. This study was designed using a 2Ã—2 factorial completely randomized design with 5 replications on 20 late-pregnant ewes. The first factor was two levels of sunflower seed oil (4% and 6%) and the second factor was the levels of black tea extract addition (0 ppm and 500 ppm). Data were analyzed by using analysis of variance (ANOVA) and Duncanâ€™s multiple range test. Results showed that supplementation of sunflower seed oil and black tea extract had no effect on physiological responses and blood profiles of ewe during late pregnancy until early lactation except for erythrocyte numbers. Erythrocyte numbers were higher on 6% sunflower seed oil supplementation than that of 4% (P<0.05). In conclusion, addition of black tea extract in diets containing 4% and 6% sunflower seed oil limitedly affect physiological responses and blood profiles of ewe.